PEMBUATAN KAIN JUMPUTAN DARI KAIN PRIMISIMA DENGAN ZAT WARNA INDIGOSOL DAN ZAT WARNA INDIGOFERA - Titin Prihatini; Yuana Rizky Anom Sari (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2022)
This study aims to: (1) Find out the evenness of the colour of the jumputan fabric from the Indigosol dyeing primisima fabric; (2) Knowing the evenness of the colour of the jumputan fabric from the indigofera dyeing primisima fabric; (3) Knowing the sharpness of the colour on the jumputan fabric produced by Indigosol dye; (4) Knowing the results of colour sharpness on jumputan fabrics produced by Indigofera dyes. The research method used is the Comparative method because this study produces products and then compares them. The subjects of this study were jumputan fabric from primisima fabric with indigosol staining and jumputan fabric from primisima fabric with indigofera dye. The data source was obtained from data collection through the questionnaire test method with 21 panellists, namely fashion design students and employees in the maharani jumputan studio. In collecting data, the authors used three kinds of methods, namely: (1) Comparative Methods; (2) Test Questionnaires; (3) Documentation. The data analysis used is the analysis of non-statistical data with a descriptive mindset; that is, the researcher seeks to analyze the data and see and read the available tables, graphs or numbers. The author also describes the actual data and what it is in the form of words and pictures or photos, then makes a description according to the data obtained from the comparison of products I and II. Based on the results of the study: Making Jumputan Fabric from Primisima Fabric with Indigosol Dye produces even, and sharp colours, and the colouring results of Indigofera Dyes have less even and less intense colours